Interest on equity – BM&FBOVESPA strategy of reducing taxes on the profit of companies in the electric sector (Revista Brasileira de Contabilidade e Gestão, 2013)
One of the biggest problems facing businesses today it is the high cost tax imposed by the Brazilian government. After the implementation of the Real Plan, and enactment of Law no. º 9249/95, which banned the restatement of the balance sheet, the company incurred a tax expense even higher, since the deduction was banned from the effects of inflation on the tax calculation payable. The same law allowed the deduction of amounts paid or credited as Interest on Own Capital (IOC) the basis for calculating the taxable income, making it an option this planning aimed at reducing the cost of this tax. Through a descriptive study of listed companies in the electricity sector of the BM & FBOVESPA with Equity (PL) over a million dollars and that use of IOC as remuneration to shareholders, we attempt to identify this cost reduction tax through research documentary qualitative and quantitative. The results indicate a reduction in the tax cost in the order of 34% of the amount credited to shareholders in the form of interest on capital and 8% of the net profit, on average, the sample studied.
Keywords: cost tax; tax planning; interest on capital